Порівняння сироваткового та плазмового гомеостазу в динаміці фармакотерапії різними комбінаціями препаратів у літніх пацієнтів з первинною артеріальною гіпертензією II стадії у поєданні з ішемічною хворобою серця = Comparison of serum and plasma homeostasis in dynamic of pharmacotherapy with different combinations in elderly patients with primary hypertension II stage and ischemic heart disease - Shtanko, V. A.; Tofan, N. V.; Yablonskaya, V. B. (Journal of Education, Health and Sport, 2016)
Shtanko V. A., Tofan N. V., Yablonskaya V. B. Порівняння сироваткового та плазмового гомеостазу в динаміці фармакотерапії різними комбінаціями препаратів у літніх пацієнтів з первинною артеріальною гіпертензією II стадії у поєданні з ішемічною хворобою серця = Comparison of serum and plasma homeostasis in dynamic of pharmacotherapy with different combinations in elderly patients with primary hypertension II stage and ischemic heart disease. Journal of Education, Health and Sport. 2016;6(2):283-292. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46670 http://ojs.ukw.edu.pl/index.php/johs/article/view/3405 https://pbn.nauka.gov.pl/works/717179 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Порівняння сироваткового та плазмового гомеостазу в динаміці фармакотерапії різними комбінаціями препаратів у літніх пацієнтів з первинною артеріальною гіпертензією II стадії у поєданні з ішемічною хворобою серця В. А. Штанько, Н. В. Тофан, В. Б. Яблонська Одеський національний медичний університет, Одеса Резюме В даному дослідженні розглянута проблема покращення ефективності фармакотерапії шляхов вивчення сироваткових та плазмових гомеостатичних зсувів на фоні різних комбінацій препаратів у пацієнтів літнього віку з первинною артеріальною гіпертензією II стадії та ішемічною хворобою серця. За допомогою методу ЛКС-метрії виявлені та охарактеризовані особливості спектральної картини при застосуванні трьох комбінацій препаратів у пацієнтів з вищезазначеною паталогією. Ключові слова: гомеостаз, фармакотерапія, первинна артеріальна гіпертензія, ішемічна хвороба серця, лазерна кореляційна спектроскопія Comparison of serum and plasma homeostasis in dynamic of pharmacotherapy with different combinations in elderly patients with primary hypertension II stage and ischemic heart disease V. A. Shtanko, N. V. Tofan, V. B. Yablonskaya Odessa National Medical University, Odessa, Ukraine Summary In this investigation problem of pharmacotherapy efficacy improvement was observed by mean of studying plasma and serum homeostatic alterations under the influence of different combinations in elderly with primary hypertension II stage combined with ischemic heart disease. For this aim 60 elder patients were examined and treated in the University Clinic of Odessa National Medical University. Mean age of the patients was 67.2±3.8 years. Depending on prescribed treatment regimen (TR) all the patients were divided into 3 groups: lisinopril, cardiomagnil – TR I; lisinopril, bisoprolol, cardiomagnil – TR II; lisinopril, bisoprolol, indapamide, cardiomagnil – TR III. N=20 in all the groups. Laser correlation spectrometry (LCS) was special biophysical investigation method. Blood serum and plasma were investigated biomaterial. TR I led to increase of intoxication processes in both investigated liquids – serum and plasma. TR II was effective in decrease of catabolic reactions and increase of anabolic ones in plasma, but in serum it caused decrease of anabolic alterations. TR III improved serum homeostasis condition, while in plasma anabolic reactions increased but in the same time was revealed growth of intoxication processes. LCS is rather sensitive method in reflection of blood serum and plasma homeostatic condition as before the treatment as after it. It allows reveal features of spectral picture after usage of specific combination. For further confirmation of informative capacity of the method must be found out associations of the LCS results with other laboratory investigations. Keywords: homeostasis, pharmacotherapy, primary hypertension, ischemic heart disease, laser correlation spectrometry. stasis, pharmacotherapy, primary hypertension, ischemic heart disease, laser correlation spectrometry.